Pendidikan Karakter Perspektif Islam Studi Komparasi Pemikiran Muhammad Nur Suwaid, Ibnu Miskawaih Dan Al Ghazali - Muhammad Lutfi; Rafikatul Maula; Iin Zainab; Jazilurrahman Jazilurrahman (AFKARINA: Jurnal Pendidikan Agama Islam, 2021)
This research wants to know the principles of character education from an Islamic perspective according to the thoughts of Muhammad Nur Suwaid, Ibnu Miskawaih and Al Ghazali. The nature of this research is library research, namely research on literature books related to the topics discussed. The source of the data in this study is the biography of the thoughts of Muhammad Nur Suwaid, Ibn Miskawaih and Al Ghazali. Character education according to the thoughts of Muhammad Nur Suwaid, Ibnu Miskawaih and Al Ghazali is to prepare children to enter a more global era but still hold fast to the teachings of their Lord. The principles of character education are the thoughts of Muhammad Nur Suwaid, Ibnu Miskawaih and Al Ghazali who are oriented towards the nature of the child.